The role of physical education and sports in stimulating and promoting voluntary work among middle school students from the point of view of students in some middle schools in the Gulf state - Abdelaziz, Idrenmouche; Lakhdar, Bouali; Abdelhamid, Berdai; Aissa, Bekli (The International tax journal, 2025)
This research aims to identify the role of physical education and sports classes in motivating and promoting volunteer work among middle school students from the point of view of students in some middle schools in the Gulf state. It dealt with the field research procedures where the researchers used the descriptive approach because it is the appropriate approach to the research problem. As for the research sample, it was part of the research community, which consisted of (55) students at the intermediate stage of some of the Gulf state averages, where the sample number was (30) students. The researchers used the SPSS statistical bag to process the raw data of the research sample. After the completion of the research procedures, the researchers processed the results statistically and then discussed the results, as for the most important conclusions and recommendations, as it was proved that there is a statistically significant correlation between the role of physical education and sports class and motivation and promotion of voluntary work among middle-school students.